Efficiency of Ceramic Composite Filter Produced Using Nano Particulate Carbonaceous Material - Adeyinka-Aderanti, Adedayo Deborah; Agbeleye, Ademola Abiona; Agunbiade, Folusho Oyedotun; Agunsoye, Johnson Olumuyiwa (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Millions of people have no access to safe water. This has led to continued incidence of waterborne diseases with severe cases of complications and sometimes death. Attempts to use silica sand-based materials for the production of filters by researchers are still evolving. In this study a novel hybrid clay-nanoparticulate agro-waste blend water filter with appropriate pore size and flow rate for contaminant-free water filtration was produced. The composite filters were produced using hydraulic pressing and sintering process. Four different ratios of clay, activated carbon and nanoparticle coconut shell (60:30:10, 60:20:20, 60:10:30, and 60:0:40 wt %) were mixed and fired at 700 °C, 750 °C, 800 °C, 850°C, 900 °C, 950 °C, and 1000 °C respectively at the rate of 75 °C/hr. E. Coli, Total Coliform, and turbidity tests were carried out on the influent water collected from Lagos Lagoon, and effluent water samples were filtered using the produced samples. The result of water tests revealed that all the filters produced removed between 86.81 % to 99% Escherichia Coliform (E. coli), and 81.81% to 93.31%% total coliform in the water sample. The blend of 60:10:30 fired at 850 °C and 900 °C showed improved properties with a flow rate value of 2.83 l/hr and 2.77 l/hr. In conclusion, the study established that synthesis of nanoparticle coconut shell and activated carbon is a suitable material for producing clay composite filters that can purify water to Nigerian Standards for Drinking Water Quality (NSDWQ) acceptable level.